Regulation of the interleukin-1 beta (IL-1 beta) gene by mycobacterial components and lipopolysaccharide is mediated by two nuclear factor-IL6 motifs. - Zhang, Y (1993)
The cytokines interleukin-1 beta (IL-1 beta) and tumor necrosis factor alpha (TNF-alpha) are released by mononuclear phagocytes in vitro after stimulation with mycobacteria and are considered to mediate pathophysiologic events, including granuloma formation and systemic symptoms. We demonstrated that the Mycobacterium tuberculosis cell wall component lipoarabinomannan (LAM) is a very potent inducer of IL-1 beta gene expression in human monocytes and investigated the mechanism of this effect. We localized the LAM-, lipopolysaccharide (LPS)-, and TNF-alpha-inducible promoter activity to a -131/+15 (positions -131 to +15) DNA fragment of the IL-1 beta gene by deletion analysis and chloramphenicol acetyltransferase assay. Within this DNA fragment, there were two novel 9-bp motifs (-90/-82 and -40/-32) with high homology to the nuclear factor-IL6 (NF-IL6) binding site. Site-directed mutagenesis demonstrated that the two NF-IL-6 motifs could be independently activated by LAM, LPS, or TNF-alpha and that they acted in an orientation-independent manner. DNA mobility shift assay revealed specific binding of nuclear protein(s) from LAM-, LPS-, or TNF-alpha-stimulated THP-1 cells to the NF-IL6 motifs. We conclude that the two NF-IL6 sites mediate induction of IL-1 beta in response to the stimuli LAM, LPS, and TNF-alpha.